Propuesta para el fortalecimiento del plan de gestión integral de residuos sólidos en la empresa Palmas del Shanusi S.A - Gutierrez Solano, Marco Antonio (2013)
This research analyzes the impact of processes of participation of workers in company Shanusi Palms S.A., in the management of industrial so lid waste (RSI) between fienes from 2012 to 2013, seeking to identify which is the potential of these participatory processes to promote the involvement of the population of workers in the environmental policies of the company Shanusi palms. S.A. The results obtained from samples collected in this study have been confined in landfills by security and part of it is reused as organic fertilizer, which exposes to risks and effects of pollution so far, one ofthe main reasons for this situation is because it has no management tool to guide and help improve the management of the waste in their various stages of managementaddress this need, has developed technical guidelines to the management the rational environmental of industrial so lid waste both for generators as well as for operators of waste developed its operational activities in the collection, transportation and recycling basic activities. In the implementation of this proposal for the strengthening of the integrated waste management Plan in Palmas de Shanusi s.a., had very good results, so that industry Shanusi Palms S.A., it was possible to quantify the actual amount of its waste, which allowed to have recourse to develop minimization and management programs.